Formação continuada sobre alienação parental a profissionais da psicologia: um estudo em EAD - Soma, Sheila Maria Prado (2018)
Parental Alienation (PA) refers to the behaviors of a parent or family member (alienator) who initiates a defamatory campaign directed at the other parent (alienated), to hinder or prevent the contact of the family member with the child. PA has a scarce number of scientific studies in Brazil and is considered controversial by the scientific literature in spite of the fact that this country has a Federal Law on the subject. Despite the lack of data in the area,forensic professionals, especially psychologists, are called to act in PA cases, and may not be prepared to do so. Thus, the present dissertation has aimed to investigate the familiarity of Brazilian psychologies with PA and how they would use the concept in simulataed cases to subsequentely plan, and evaluate an online training course on the subject, with the purpose of filling possible gaps in the training of suchprofessionals, helping them improve their practices. The results of the dissertation are presented in four scientific papers: the first one refers to an already published review study of Brazilian publications on PA which analyzed 13 studies, verifying that most of them referred to theoretical constructs with questionable validity. The second article evaluated, through an online survey, the concepts of 137 Brazilian psychologists about PA and how they would apply such concept in simulated cases, concluding, among other aspects, that although participants admitted familiarity with the term, they presented difficulties in a case study vignette that with interface with child sexual abuse, demonstrating the need for further training in the area. Article 3 aimed to develop and provide an online PA training and its effectiveness in performance of 40 psychologists in termos of comparison with a PA questionnaire before and after the training. Among the results, statistical significance was found mainly in relation to an increase of familiarity with PA. The fourth and last paper, conducted a social evaluation of 38 psychologists who took the online course. Results pointed out that participants evaluated the training as positive and enriching for their practices. Half of participants presented personal difficulties which were mostly related to personal time management, as well as using resources from the online plataform. Finally, the dissertation unveils the controversial topics associated with PA and the complexity of assessing alegations at risk of minimizing claims of the severe problem of child sexual abuse. In addition, the present work evaluates a pioneer attempt to conduct online training to Brazilian psychologists on PA, which may be a starting point for new empirical studies on the subject, particularly on continuing education to professionals on parental alienation.